Clinical Diagnosis and Perioperative Management of Glioma-Related Epilepsy - You, Gan; Sha, Zhiyi; Jiang, Tao (Frontiers in Oncology, 2021)
Gliomas account for more than half of all adult primary brain tumors. Epilepsy is the most common initial clinical presentation in gliomas. Glioma related epilepsy (GRE) is defined as symptomatic epileptic seizures secondary to gliomas, occurring in nearly 50% in high-grade glioma (HGG) patients and up to 90% in patients with low-grade glioma (LGG). Uncontrolled seizures, which have major impact on patients’ quality of life, are caused by multiple factors. Although the anti-seizure medications (ASMs), chemotherapy and radiation therapy are also beneficial for seizure treatment, the overall seizure control for GRE continue to be unsatisfactory. Due to the close relationship between GRE and glioma, surgical resection is often the treatment of choice not only for the tumor treatment, but also for the seizure control. Despite aggressive surgical treatment, there are about 30% of patients continue to have poor seizure control postoperatively. Furthermore, the diagnostic criteria for GRE is not well established. In this review, we propose an algorithm for the diagnosis and perioperative management for GRE.